Comparing accuracy between global positioning systems and ultra-wideband-based position tracking systems used for tactical analyses in soccer - Bastida-Castillo, A.; Gómez-Carmona, C. D.; De La Cruz Sánchez, E.; Pino-Ortega, J. (European Journal of Sport Science, 2019)
Current studies have reported high accuracy in global positioning system (GPS) and recently developed ultra-wideband (UWB)-based tracking systems for monitoring time - motion patterns. The accuracy and reliability of both systems may be different in tactical analysis application, an aspect that has never been studied previously. The aims of the present study were: (i) to determine and compare the accuracy of GPS and UWB technologies in soccer players` positions (ii) to compare the tactical application of both systems. Following institutional ethical approval and familiarisation, 14 well-trained soccer players performed tests around five courses: (a) field perimeter, (b) halfway line, (c) centre circle, (d) perimeter of the penalty area, and (e) semicircle penalty area. Also, a small-sided game was played monitored with WIMUPRO™ to determine real and practical differences in accuracy of both systems in tactical analysis. For the GPS, the mean absolute error (N = 9445) of "x" and "y" coordinates was 41.23 ± 17.31 cm and 47.6 ± 8.97 cm, respectively. For UWB, it was 9.57 ± 2.66 cm and 7.15 ± 2.62 cm. The results of the "x" and "y" accuracy comparison were significantly lower in all cases (p < 0.05) with an ES of 0.78 and 0.95, respectively. In a real practical application, the differences of both systems reached 8.31% in typical tactical variables (ES = 0.11). In contrast to GPS-10Hz, UWB WIMUPRO™-20 Hz has been demonstrated to be an acceptable technology to estimate the position of players on the pitch with high accuracy and be a useful, automatic, and portable instrument for tactical analysis measurement.